(untitled) (Journal-of-Ethiopian-Church-Studies/የኢትዮጵያ-ቤተ-ክርስቲያን-ጥናት-መጽሔት-Live, 2016)
This study aims to introduce the history, architecture, and conservational status of Nazugn Maryam and Abunä Aron, two of the many rock-hewn churches found in Mäqét District, North Wällo. Nazugn Maryam is a monolithic structure believed to have been built during the 4th century A.D. The externally sculpted vertical buttresses; the pointed, semi-circular, opened and false windows; and the horizontal supporter are among the architectural distinctions of this church. It also has an elaborate drainage system via south-westerly and north-easterly tunnels. Such features suggest continuity in the architectural tradition of the country and make Nazugn Maryam comparatively pertinent to the stylistic and engineering apogee attained in the rock-hewn churches of Lalibela. Abunä Aron, on the other hand, takes its name from an Ethiopian monk who built the church in the 14th century. This cave church has a complex layout constituting seven divisions. Its most amazing feature is, however, the sәqurät (ስቁረት), a waterproof aperture on the roof of the chanting, which attests to the architectural excellence of the hewer. Despite the historical and architectural significance of the two churches, they remained isolated from the discussion of rock-hewn churches in the country partly due to their geographical inaccessibility. This study endeavors to fill the lacunae by identifying challenges related to anthropogenic and natural factors, as well as indicating the urgent need for conservation. It also provides information useful to promote the churches to believers, researchers, and heritage management officials.